Microfluidic electronic tongue - Daikuzono, Cristiane M.; Dantas, Cleber A. R. [UNESP]; Volpati, Diogo [UNESP]; Constantino, Carlos J. L. [UNESP]; Piazzetta, Maria H. O.; Gobbi, Angelo L.; Taylor, David M.; Oliveira, Osvaldo N.; Riul, Antonio (Elsevier B.V., 2015)
Fast, simple inspection of liquids such as coffee, wine and body fluids is highly desirable for food, beverage and clinical analysis. Electronic tongues are sensors capable of performing quantitative and qualitative measurements in liquid substances using multivariate analysis tools. Earlier attempts to fulfil this task using only a few drops (microliters) of sample did not yield rational results with non-electrolytes e.g. sucrose (sweetness). We report here the fabrication and testing of a microfluidic e-tongue able to distinguish electrolytes from non-electrolytes, covering also the basic tastes relevant to human gustative perception. The sensitivity of our device is mainly attributed to the ultrathin nature of an array formed by non-selective sensing units. The electronic tongue is composed of an array of sensing units designed with a microchannel stamped in a poly( dimethylsiloxane) (PDMS) matrix and sealed onto gold interdigitated electrodes (IDEs). The IDEs are then coated in situ with a 5-bilayer film deposited by the layer-by-layer (LbL) technique. The cationic layer is derived from polyallylamine chloride (PAH). The anionic layer is either poly(3,4-ethylenedioxythiophene)-poly( styrenesulfonate) PEDOT:PSS, polypyrrole or nickel tetrasulfonated phthalocyanine. When compared to a conventional electronic tongue our system is three times faster and requires only microliters of sample. Applying Principal Component Analysis to the data yields a high correlation for all substances tested. This microfluidic e-tongue has the potential for producing low-cost, easily integrated, multi-functional sensor for food, beverages, in addition to clinical and environmental applications.
Keywords: Microfluidics; Layer-by-layer; Electronic tongue